The Impact of Positive Youth Development among Adolescents Attending Secondary Schools in Enugu, Nigeria: A Cross-Sectional Study - Vivian O. Onukwuli; Awoere T. Chinawa; Jude T. Onyia; Francis N. Ogbuka; Josephat M. Chinawa (International Journal of Medicine and Health Development)
Background: Positive youth development (PYD) programs can have a positive impact on adolescents’ lives, leading to improved academic performance, better mental health outcomes, and reduced risk behaviors. Objectives: To document different aspects of PYD programs and the associated factors among adolescents who attend secondary schools in the Enugu metropolis. Materials and Methods: This was a cross-sectional study. A three-stage sampling technique was used to select 400 adolescents from seven secondary schools in Enugu State, Nigeria. An assessment of PYD was made using the PYD Youth Collaboratory Questionnaire. The chi-square statistic was used to assess the distribution of PYD domains using demographic information. Results: The correlation of the PYD domains shows that confidence has a statistically significant positive correlation with character (r = 0.303, P = 0.010), connection (r = 0.537, P = 0.010), competence (r = 0.558, P = 0.010), and overall PYD (r = 0.727, P = 0.010). Females have significantly higher scores on PYD (87.3%) than males (75.9%) (P = 0.005). Students in senior secondary class 2 (SS2) have the highest scores on PYD (89.9%), while SS3 students have the lowest (64.9%) (P = 0.002). The occupation of the mothers showed significant differences, with petty traders, laborers, and messengers having the highest scores on PYD (92.4%) (P < 0.001). Conclusion: This study highlights a high prevalence of PYD among secondary school adolescents, with females scoring higher in all domains. Although connection and competence showed strong positive results, character was notably lower, potentially linked to family dynamics. The findings suggest that fostering connectedness and character development may enhance PYD outcomes.